INFLUENCE OF ORGANIC BIOBACTERIAL FERTILIZER ON CORN CULTURE ON THE EXAMPLE OF KAKHETI REGION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Among cereal plants, corn is one of the most important crops. Corn is highly productive and is used for both food and food production. The milk-wax crop is a nutritious and highly absorbent concentrated feed for animals.Corn kernels are widely used in food production to make cereals, flour and other food products. Corn is the best raw material in the production of alcohol, starch, glucose, beer and canning industry. It is used to make high quality oil, used in the production of textiles and paper.